Physical activity modifies the influence of apolipoprotein E ε4 allele and type 2 diabetes on dementia and cognitive impairment among older Mexican Americans. Issue 1 (7th July 2017) - Shih, I‐Fan; Paul, Kimberly; Haan, Mary; Yu, Yu; Ritz, Beate
Abstract: Introduction: The etiologies of dementia are complex and influenced by genetic and environmental factors including medical conditions. Methods: We used Cox regression model to estimate the individual and joint effects of physical activity (PA), apolipoprotein E ( APOE ) ε4, and diabetes status on risk of dementia and cognitive impairment without dementia (CIND) among 1438 cognitively intact Mexican American elderly who were followed up to 10 years. Results: The risk of developing dementia/CIND was increased more than threefold in APOE ε4 carriers or diabetics with low levels of PA compared with ε4 noncarriers or nondiabetics who engaged in high PA (ε4: hazard ratio [HR] = 3.44, 95% confidence interval [CI] = 1.85–6.39; diabetes: HR = 3.11, 95% CI = 1.87–5.18); the presence of all three risk factors increased risk by nearly 10‐fold (HR = 9.49, 95% CI = 3.57–25.3). Discussion: PA in elderly Hispanics protects strongly against the onset of dementia/CIND, especially in APOE ε4 carriers and those who have diabetes. Highlights: ‐ Physical activity (PA) reduces the risk of cognitive impairment in older Hispanic. ‐ Joint effects of low PA and apolipoprotein E ε4 on cognition impairment is strong. ‐ PA protects against cognitive impairment strongly in ε4 carriers with diabetes.